STUDI LITERATUR EFEKTIFITAS PEMBERIAN KONSELING TERHADAP KEPATUHAN PASIEN HIPERTENSI DI BERBAGAI FASILITAS KESEHATAN - Nida Anshofia Indriani; Herda Ariyani; Maria Ulfah (JCPS (Journal of Current Pharmaceutical Sciences), 2021)
Various evidence states that counseling carried out by pharmacists can improve adherence to taking medication in hypertensive patients and even improve the outcome of therapy. This study aims to determine the effectiveness of counseling on the compliance of hypertensive patients in various health facilities. The research method used is the literature study method which is carried out by searching for scientific evidence and collecting literature from various trusted databases, namely Scince Direct, Scopus Google Scholar, Elsavier, SINTA. There are 12 literatures used in this study, consisting of 8 national journals indexed by SINTA 1-4, 2 international journals indexed by SCOPUS and 2 Proceedings of the research. The results showed that counseling provided by pharmacists were significant in increasing adherence, controlling sodium, fat intake and lowering blood pressure also improving the quality of life of patients. This research is expected to be material for further research on counseling to increase the effectiveness of therapy and can be an input for future government policies in overcoming hypertension emergencies so as to add strategies in providing effective pharmaceutical care counseling.